Impact of globalization on unemployment in Sub-Saharan African (SSA) countries - Peter, Adamu; Kaliappan, Shivee Ranjanee; Mhd Bani, Nor Yasmin; Mohamed Nor, Norashidah (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This study examined the impact of globalization on unemployment in 35 countries in Sub-Saharan African for the period 2007-2014. The study period and number of countries used are based on data availability. The system generalized method of moments estimation technique was applied because unemployment is considered a dynamic phenomenon. The empirical findings shows that aggregated globalization measures (economic, social and political) significantly impact unemployment rate in SSA while among the components of globalization, only political globalization reduces unemployment. Economic growth rate and labor market regulations are significant and negatively related to unemployment while wage rate and inflation increases the rate of unemployment. Maintaining a low level of inflation is key to address the unemployment problems because the results suggest that stagflation exist in the case of SSA at the moment. Therefore, policies aimed at reducing the rate of unemployment should focus on low inflation rate, political globalization, labor market regulation and economic growth. Policies should also ensure that the regulations of the labor market are more flexible so as to benefit from globalization which can impact significantly on unemployment rate.